Um estudo sobre os impactos contábeis e econômicos da marcação a mercado dos investimentos de longo prazo na definição do déficit, equilíbrio ou superávit atuarial dos fundos de pensão no Brasil (IAS 19 e IAS 26) - Pádua, Rosana Passos de (2018)
Brazil is facing many discussions about the future of social security, and in this context, complementary social security becomes even more relevant; due to this, a great interest arose in studying the accounting of pension funds in the light of Brazilian and international rules, IAS 19 and IAS 26. The research problem consisted in understanding and seeking alternatives to the difficulty of pension fund managers to comply with the rules of the financial market and to mark-to-market for long-term investments with the current conditions of interest rate volatility, in the same time there is no mark-to-market of actuarial liabilities, causing an actuarial mismatching. The research was conducted through a case study based on a six-year pension fund financial statement and the outcome of the case study demonstrated that a possibility to minimize this effect and reduce the risk of sponsors and participants being called to cover the deficits, would be the accounting of the counterpart of the mark-to-market of the asset in a transitional liability account as a provision, without impacting the results of the pension funds